Abrupt events and population synchrony in the dynamics of Bovine Tuberculosis - Moustakas, Aristides; Evans, Matthew R; Daliakopoulos, Ioannis N; Markonis, Yannis (Nature communications, 2018)
Disease control strategies can have both intended and unintended effects on the dynamics of infectious diseases. Routine testing for the harmful pathogen Bovine Tuberculosis (bTB) was suspended briefly during the foot and mouth disease epidemic of 2001 in Great Britain. Here we utilize bTB incidence data and mathematical models to demonstrate how a lapse in management can alter epidemiological parameters, including the rate of new infections and duration of infection cycles. Testing interruption shifted the dynamics from annual to 4-year cycles, and created long-lasting shifts in the spatial synchrony of new infections among regions of Great Britain. After annual testing was introduced in some GB regions, new infections have become more de-synchronised, a result also confirmed by a stochastic model. These results demonstrate that abrupt events can synchronise disease dynamics and that changes in the epidemiological parameters can lead to chaotic patterns, which are hard to be quantified, predicted, and controlled.
Keywords: Cattle; Animals; skot; United Kingdom; Models, Statistical; Epidemiological Monitoring; Tuberculosis, Bovine; statistické modely; Spojené království; Stochastic Processes; tuberkulóza skotu; Incidence; Disease Outbreaks; epidemiologické monitorování; incidence; Mycobacterium bovis; stochastické procesy; epidemický výskyt choroby; zvířata; Spatio-Temporal Analysis; časoprostorová analýza